2015
DOI: 10.1111/apt.13090
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: patient-reported outcomes in chronic hepatitis C - the impact of liver disease and new treatment regimens

Abstract: Summary Background Treatment for chronic hepatitis C (CH‐C) is rapidly changing and moving away from an interferon and ribavirin‐based therapy to interferon‐free ribavirin‐free all oral regimens. These regimens are simpler and shorter to administer with very high efficacy rates and better side effect profiles. As advances in the treatment of CH‐C occur, it is imperative to capture both clinical outcomes (efficacy and safety) as well as patient‐reported outcomes (PROs). In fact, PROs assesses and quantifies the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
189
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(206 citation statements)
references
References 117 publications
(594 reference statements)
17
189
0
Order By: Relevance
“…Mathematical modelling also indicates that DAA treatment of PWID is cost-effective, given the prevention benefit . At an individual level, successful treatment of HCV infection improves health-related quality of life (Younossi & Henry, 2015), reduces the progression of liver disease (Grebely & Dore, 2011) and reduces all-cause mortality in people with advanced liver disease (van der Meer, et al, 2014).…”
Section: Hcv Treatment For Pwidmentioning
confidence: 99%
“…Mathematical modelling also indicates that DAA treatment of PWID is cost-effective, given the prevention benefit . At an individual level, successful treatment of HCV infection improves health-related quality of life (Younossi & Henry, 2015), reduces the progression of liver disease (Grebely & Dore, 2011) and reduces all-cause mortality in people with advanced liver disease (van der Meer, et al, 2014).…”
Section: Hcv Treatment For Pwidmentioning
confidence: 99%
“…Obtaining information during treatment on the likelihood of treatment success through viral load testing was identified in one study as an adherence motivator 44. While experience of hepatitis C-related stigma, often related to a history of injecting drug use, was also associated with medication adherence 42,45. Sublette et al42 found that participants reported feeling “unclean” and “embarrassed about divulging their status to doctors and dentists”, but this stigma disappeared once they had been cured of hepatitis C 42.…”
Section: Assessing and Supporting Patient Adherence With Daasmentioning
confidence: 99%
“…It is also important to collect patient-reported outcomes, especially ones that capture patients' energy and physical components. Hepatitis C (HCV) infection has a considerable negative impact on patient-reported outcomes (PRO) and patients' WP [2]. Numerous manifestations of HCV lead to an economic burden related to the complications and extrahepatic manifestation, thus decreasing WP [3].…”
Section: Introductionmentioning
confidence: 99%